Designing games : a guide to engineering experiences - Sylvester, Tynan (Sebastopol (CA) : O'Reilly, 2013)
How do video games resonate with players to become worldwide hits? This practical book shows you how the right combination of story elements, psychology, and game theory can generate emotionally charged experiences that take players beyond mindless entertainment.
Includes bliographical references and index.
Keywords: Video games. -- Design. -- Psychological aspects; Computer games. -- Design; Computer games. -- Psychological aspects; videopelit; tietokonepelit; suunnittelu; psyykkiset vaikutukset; psykologia; peliteollisuus; videospel; datorspel; planering; psykiska effekter; psykologi; spelindustri